ChemInform Abstract: Broad‐Spectrum Liquid‐ and Gas‐Phase Decontamination of Chemical Warfare Agents by One‐Dimensional Heteropolyniobates. Issue 35 (August 2016) - Guo, Weiwei; Lv, Hongjin; Sullivan, Kevin P.; Gordon, Wesley O.; Balboa, Alex; Wagner, George W.; Musaev, Djamaladdin G.; Bacsa, John; Hill, Craig L.
Abstract: A wide range of chemical warfare agents and their simulants are catalytically decontaminated by K12 [Ti2 O2 ] [GeNb12 O40 ]·19H2 O under mild conditions and in the dark.